2013
DOI: 10.1016/j.ijscr.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Gouty arthritis at interphalangeal joint of foot after sildenafil use: A case report

Abstract: Sildenafil use may cause gouty arthritis, and surgical decompression may be helpful for definitive diagnosis and symptom relief in atypical presentation of gout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Following surgical decompression, pharmacological treatment and lifestyle modifications are of paramount importance. 5 In our report, there was a chronic gout case refractory to the treatment. Skin ulceration and discharge developed, and the patient significantly benefited from the surgical decompression and pharmacological treatment.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Following surgical decompression, pharmacological treatment and lifestyle modifications are of paramount importance. 5 In our report, there was a chronic gout case refractory to the treatment. Skin ulceration and discharge developed, and the patient significantly benefited from the surgical decompression and pharmacological treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Although the triggering mechanism of the acute attack has been poorly understood, factors for the development of gout have been described (4). These include an increased level of uric acid, alcohol abuse, hypertension, the use of antihypertensives, increased body mass index (BMI) and familial history of gout (5). In addition, it has been reported that gout may be associated with persistent psoriasis especially in male patients and in those with other causes of hyperuricemia (6).…”
mentioning
confidence: 99%
“…It is also worth mentioning that two case reports of acute gouty arthritis occurring following intake of sildenafil [ 130 , 131 ], a phosphodiesterase type 5 inhibitor (PDE5i), used in the treatment of erectile dysfunction. While these case reports have been extraordinarily rare, and more studies are therefore needed in these regards, this evidence should drive clinicians toward careful use of PDE5i in patients with gout, or possibly even asymptomatic hyperuricemia.…”
Section: Resultsmentioning
confidence: 99%
“…It was hypothesized that her pregnancy resulted in insulin resistance, reducing the renal excretion of urate, and eventually provoked the flare. Alici et al [14] presented a case of a 58-year-old hypertensive man with several episodes of pain and swelling in the first interphalangeal joint of the right great toe. The appearance and recurrence of symptoms occurred after sildenafil was used, and there were no symptoms after withdrawal of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…According to the available literature [10][11][12][13][14][15][16][17][18][19], gouty arthritis usually occurs in patients with hyperuricemia and it can be induced by a variety of factors. Here, we describe a case of acute gouty arthritis attacks caused by a great toe injury, which was successfully treated with benzbromarone and ibuprofen.…”
Section: Introductionmentioning
confidence: 99%